Keseimbangan Relasi Orang Tua–Remaja sebagai Prediktor Kejelasan Orientasi Masa Depan Pendidikan - Awit Marwati Sakinah (Psympathic : Jurnal Ilmiah Psikologi, 2016)
Future orientation is formed as a result of interaction with the environment one of them teenage parents. The study aims to determine the effect balance relationship patterns of parent-adolescent to the orientation of future education in adolescents of Bandung city. The analysis technique used is the correlation analysis and logistic regression. The study use cluster sampling to obtain a sample of 358 students. The results showed that the balance relations on the dimensions of adaptability and cohesion have a greater influence on the clarity of the future orientation of youth education in Bandung. Balance relationship patterns of parent-adolescent balance has possibility of 16.181 times more clearly educational future compared with the balance of relationship patterns of parent-adolescent unbalance. Balance relationship patterns of parent-adolescent has possibility of 2.088  times more clearly educational future compared with the balance of relationship patterns of parent- adolescent to mid range category.